Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s00438-018-1492-8
|View full text |Cite
|
Sign up to set email alerts
|

The influence of paternal diet on sncRNA-mediated epigenetic inheritance

Abstract: The risk of developing metabolic diseases is conferred by genetic predisposition from risk genes and by environmental exposures that can manifest in epigenetic changes. The global rise in obesity and type II diabetes has motivated a search for the epigenetic factors underlying these diseases. The possibility of transgenerational inheritance of epigenetic changes raises questions regarding how spermatozoa transmit acquired epigenetic changes that affect the metabolic health of the next generation. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…There is a growing appreciation for the importance of the paternal preconception environment in the developmental programming of offspring 1 , 15 , 44 , 48 51 . Though the mechanisms underlying this developmental plasticity are likely adaptive, in the context of human health, these effects may be expressed as changes in disease risk or resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing appreciation for the importance of the paternal preconception environment in the developmental programming of offspring 1 , 15 , 44 , 48 51 . Though the mechanisms underlying this developmental plasticity are likely adaptive, in the context of human health, these effects may be expressed as changes in disease risk or resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies focusing on the influence of preconception paternal insults implicate epigenetic processes important for germ cell development and maturation 17 46 . Advances in high-throughput next-generation sequencing have revealed highly complex populations of RNA in sperm, and in animal studies, small noncoding RNA (sncRNA) populations have emerged as causal agents in the germline transmission of paternal experience 44 , 47 51 . Animal studies have provided the strongest evidence that paternal experiences, including various types of stress, drugs, and dietary manipulations, are associated with lasting changes in sperm RNA expression, where changes in specific miRNA and tRNA fragments have often been reported 17 25 , 27 , 28 , 31 , 32 , 36 38 , 40 , 41 , 52 , 53 .…”
Section: Introductionmentioning
confidence: 99%
“…Although emerging evidence indicates that sncRNA in spermatozoa may serve as an important channel of epigenetic information transfer to the next generation, our knowledge of factors that affect sperm sncRNA profiles is only starting to emerge. For examples, existing research identified that high-fat diets and low-protein diets can alter the expression of miRNA, piRNA, and tRNA-derived RNA in spermatozoa (reviewed in [ 51 ]). Diet-induced changes in the sncRNA profile were associated with phenotypes displaying insulin resistance, altered body weight, and glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al ( 2017 ) used DNA methylation to find cancer subtypes on breast cancer. Pan et al ( 2018 ) used copy number variants to identify four cancer subtypes on breast cancer. Zhao et al ( 2009 ) used single-stranded DNA (ssDNA) to find cancer subtypes on lung cancer.…”
Section: Introductionmentioning
confidence: 99%